Physiological assessment of 2 color strains of Crassiphycus corneus (J. Agardh) Gurgel, J.N. Norris et Fredericq (Gracilariales, Rhodophyta): Effects of temperature and irradiance - Jofre, Jocelyn; Navarro Martinez, Nelso Patricio; Plastino, Estela María (My University, 2020)
Abstract Crassiphycus corneus (J.Agardh) Gurgel, J.N.Norris et Fredericq (Gracilariales, Rhodophyta) is a species with high-quality and high yields of polysaccharides and is therefore an important agarophyte on the west coast of the Atlantic Ocean. On the northeastern coast of Brazil, the populations of this species are mostly composed of individuals of the wild red color strain and some individuals of the green color strain, the latter being scarcely studied. This work characterizes and compares the physiological performance of the wild red strain and the green variant under different temperature and irradiance conditions in the laboratory. The results indicate that the green and red strains are similarly tolerant to low temperatures (18 °C) but intolerant to high temperatures (35 °C). Both strains exhibited the highest growth rate at 25 °C and high irradiance (500 μmol photon·m-2·s-1). Under these conditions, photosynthetic rate and pigment content were similar in both color strains, but growth rates were higher in the red strain. Despite this difference, it is important to highlight that the green strain showed a growth rate of over 10%, which indicates that it could be used for cultures aiming to obtain products with added value.
Keywords: physiology; crassiphycus corneus; mariculture; photosynthesis; pigments